Investigating the Complex Relationship between Financial Performance and Company’s Green Behavior: A Comparative Analysis - Wenyao Zhang; Ruzhi Xu; Lu Wang (Discrete Dynamics in Nature and Society)
Under the new normal of economy, the relationship between economic benefits and company’s environmental behavior (green behavior) has long been the focus of scholars’ research, but less attention has been paid to the effect of financial performance on company’s green behavior in China as a developing country. Thus, by adopting a mixed methodology, we conduct a quantitative study by selecting 228 companies as samples with good and poor green behavior for comparative analysis, followed by a qualitative study of 20 specific cases, to analyse the complex relationship mechanism of how financial performance in terms of business solvency, profitability, and development ability affect company’s green behavior. The results indicate that business solvency, profitability, and development ability are strongly associated with company’s green behavior, respectively. This study contributes to the green behavior literature.